2007
DOI: 10.5210/fm.v12i10.1964
|View full text |Cite
|
Sign up to set email alerts
|

Using a Tetradic Network Technique and a Transaction Cost Economic Analysis to illustrate an economic model for an open access medical journal

Abstract: There is a crisis in scholarly publishing. The value of the scholarly information is frequently much less than the cost of providing that information. Consequently, libraries are suffering and scholars do not have access to information that they need. However, certain for-profit publishers and scientific societies are benefiting substantially from the current system. The Internet has demonstrated the potential to change this structure. The Budapest, Berlin and Bethesda initiatives show there is significant wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mills, et al (2007), using a tedratic network technique and a transaction cost analysis to compare a traditional subscription, print-based medical journal with an open access medical journal, found that total transaction costs were reduced by a factor of between five and 10 for the open access journal. The cost of producing an article in the print/subscription journal was US$2,500, while an equivalent open access article was US$500.…”
Section: Affordabilitymentioning
confidence: 99%
“…Mills, et al (2007), using a tedratic network technique and a transaction cost analysis to compare a traditional subscription, print-based medical journal with an open access medical journal, found that total transaction costs were reduced by a factor of between five and 10 for the open access journal. The cost of producing an article in the print/subscription journal was US$2,500, while an equivalent open access article was US$500.…”
Section: Affordabilitymentioning
confidence: 99%
“…Recent arguments favor cutting publishing cost through accessing funds from institutions, organizations and individuals who fund research. Universities are also been called upon to intensify their contributions and funds to the growth of the open access initiative (Mill et al, 2007). Also, scholars and practitioners have worked on developing better economic models to justify the cost effectiveness of the open access initiative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…WN12 Management Tenure Yes Does increase in Yes x x x x x x No Yes Management Tenure What is the tenure of the whole-network increase BE, LCE, management team in months? (E.g., [1][2][3][4][5][6][7][8][9][10][11]SI,60+) Validity: This variable seemed valid for all sites. Tenure was readily measurable through site records.…”
Section: \mentioning
confidence: 99%